Analysis of a Wide Voltage Hybrid Soft Switching Converter - Bor-Ren Lin (Electronics, 2021)
A hybrid PWM converter is proposed and investigated to realize the benefits of wide zero-voltage switching (ZVS) operation, wide voltage input operation, and low circulating current for direct current (DC) wind power conversion and solar PV power conversion applications. Compared to the drawbacks of high freewheeling current and hard switching operation of active devices at the lagging-leg of conventional full bridge PWM converter, a three-leg PWM converter is studied to have wide input-voltage operation (120–600 V). For low input-voltage condition (120–270 V), two-leg full bridge converter with lower transformer turns ratio is activated to control load voltage. For high input-voltage case (270–600 V), PWM converter with higher transformer turns ratio is operated to regulate load voltage. The LLC resonant converter is connecting to the lagging-leg switches in order to achieve wide load range of soft switching turn-on operation. The high conduction losses at the freewheeling state on conventional full bridge converter are overcome by connecting the output voltage of resonant converter to the output rectified terminal of full bridge converter. Hence, a 5:1 (600–120 V) hybrid converter is realized to have less circulating current loss, wide input-voltage operation and wide soft switching characteristics. An 800 W prototype is set up and tested to validate the converter effectiveness.